A cantoria de viola na contemporaneidade: seus poetas em performance e memórias; estratégias para formação poética de apologistas e repentistas - Nóbrega, Marcelo Vieira da (2020)
The cantoria de viola, poetic art that constitutes the creation of improvise verses by a couple of repentistas - established in the Brazilian Northeast from the beginning of the 19th century - motivated especially by the impulse of the new social media, goes through a special moment. The placement of programs that involve the improvising art, through 'lives' of radio stations on the internet, as well as the massification of social media which deal with the theme, stimulating even more the repente art. In this context, the city of Campina Grande (PB) has revealed itself as one of the great centers of improvising viola expression. In this thesis, a Case Study and of a Participating kind, I propose to investigate this poetic expression in contemporary times, based on my experience as an apologist participating in the WhatsApp Clube do Repente group, based in this city. To this end, I have delimited a corpus of data collection based on three axes: in the first, I catalog cantoria de viola events that occurred in the geographic area between the states of Piauí, Ceará, Rio Grande do Norte, Paraíba and Pernambuco, between the months December 2017 and May 2018; in the second analysis, the poetic production of cantadores and apologists in the mentioned app above, between February and March 2018; and finally, I analyze the performances of artists from different age groups - most of whom are members of the Clube - that took place in different cantoria de viola events between 2018 and 2019. I started from the central hypothesis that this group exerts strategic importance for repente art as a forum of discussion, publicity and broadcasting of events and issues specific to viola singing, as well as a school for learning new poets and apologists of the genres most practiced in cantoria de viola. In fact, the analyzes pointed to some conclusions, among which I highlight: the increase of 'lives', on the internet, of programs by radio stations that broadcast cantoria events and / or general discussions about repente art, a fact that, little by little, it drives a new paradigm in the relations with this media: the 'see' radio replacing the 'listen' radio; Clube do Repente, as well as other WhatsApp groups spread across the Northeast, have proven to be effective media supports for boosting not only the poetic production of cantadores, but also of apologists; slight advantage, in terms of performance, of the socalled young singers (age groups A and B, up to 45 years old), when compared to those of age groups C and D (over 45 years old), in different themes. However, for the defense of motes and issues related to political party issues, most of the cantadores assumed an ideological tendency of the socalled left, with the systematic defense of the innocence of former President Lula; the vast majority of professionals live on the margins and depend on another activity to survive, with the exception of famous people who self-manage or those who depend on promoters of cantoria, which are not always well intentioned; internal disputes between singers, which involve disputes over territories, egos, envies, wages and jealousy seem to denounce a very disjointed and dispersed professional category.